Synthesis and Characterization of Oxide Conductors in Pbo-Bi2o3-M2o5 (M = V, P, As) - Lee, Chiu Sze (2004)
Materials of compositions PbBi6M2O15 and (PbO)n(BiMO4), where M = V, P, As and n = 1, 2, 4 were prepared via solid state reaction. These materials were characterised using X-ray diffraction (XRD), density measurement, inductively coupled plasmaatomic emission spectrometry (ICP-AES), ac impedance spectroscopy, differential thermal analysis (DTA), thermogravimetry analysis (TGA), Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). Complete solid solution series were obtained in the PbBi6V2O15-PbBi6P2O15, PbBi6V2O15-PbBi6As2O15 and PbBi6P2O15-PbBi6As2O15 systems. All the materials were isostructural, and crystallised in orthorhombic symmetry. However, the cell parameter a of these materials was twice those reported in JCPDS. The conductivity of these materials decreased in the order of PbBi6V2O15 > PbBi6As2O15 > PbBi6P2O15. PbBi6V2O15 is an oxide ion conductor as it has a transference number of 0.8 above 650ºC. v Substitution of Sr for Pb in PbBi6V2O15 resulted in the formation a new material of SrBi6V2O15 with higher conductivity. On the other hand, Pb in both PbBi6V2O15 and PbBi6As2O15 could be replaced by Na and Bi, resulting in the formation of NaBi13V4O30 and NaBi13As4O30. Besides successfully suppressing the phase transition observed in PbBi6V2O15, these materials had higher conductivity compared to that of PbBi6(V/As)2O15. The conductivity of these materials was in the range of ~ 10-3 ohm-1 cm-1 at 800°C. Conductivity decreased in the order of NaBi13V4O30 > SrBi6V2O15 > PbBi6V2O15. These materials appeared to be oxide ion conductors. Complete solid solution series were formed in the Pb2BiPO6-Pb2BiAsO6, Pb4BiPO8- Pb4BiVO8, Pb4BiPO8-Pb4BiAsO8 and Pb4BiVO8-Pb4BiAsO8 systems. The properties determined generally agreed with those reported; these materials were mixed oxide ion conductors. The conductivity decreased in the order of Pb2BiMO6 > PbBiMO5 > Pb4BiMO8, and V > As > P.